Exchange requirement-based delivery method of structural design information for collaborative design using industry foundation classes - Lai, Huahui; Zhou, Cheng; Deng, Xueyuan (Journal of Civil Engineering and Management, 2019)
In Architecture, engineering, and construction (AEC) collaboration, exchange requirements (ERs) vary in different projects with different platforms. In order to ensure the completeness and accuracy of data sharing and exchange for structural engineering in collaborative design, an ER-based delivery method was proposed to improve the delivery of structural design information. First, a process map of structural design was developed based on Information Delivery Manual (IDM). Within this process map, an ER Matrix of structural design was proposed to define information required by other disciplines at different stages. This matrix was composed of a set of required structural objects and their attributes, which were mapped to related Industry Foundation Classes (IFC) data. The mapping between the ER Matrix and IFC-based structural model data was implemented by an exchange model generation algorithm. Furthermore, a delivery tool was developed to define the ER Matrix in two ways, including user interface and XML-based language. A practical project was used to illustrate the utility of the proposed method. The results show that the proposed method using IFC is beneficial for structural information delivery.